OpenIPMC: A Free and Open-Source Intelligent Platform Management Controller Software - Calligaris, Luigi [UNESP] (2021)
OpenIPMC is a free and open-source software designed to implement the logic of an intelligent platform management controller (IPMC). An IPMC is a fundamental component of electronic boards conformant to the advanced telecommunications computing architecture (ATCA) standard, currently being adopted by a number of high-energy physics experiments. The IPMC is responsible for monitoring the health parameters of the board, managing its power states, and providing board control, debug, and recovery functions to remote clients. OpenIPMC is based on the FreeRTOS real-time operating system and is designed to be architecture-independent, allowing it to be used in firmware designed for a variety of microcontrollers. Having a fully free and open-source code is an innovative aspect for this kind of software, enabling full customization by the user. In this work, we present the features and structure of OpenIPMC, as well as its example implementations on Xilinx Zynq UltraScale+ (ZynqUS+), Espressif ESP32, and ST Microelectronics STM32 architectures.